أثر الوسائط التّقنية والتّكنولوجية على مسرح الثّورة - لعويجي, عمار; مليان, خولة (جامعة الوادي - university of Eloued, 2022)
تعتبر الرقمنة من أهم المواضيع في العصر الحالي ومع التطور العلمي والتكنولوجي الحاصل وكذلك تطور الوسائط التقنية وتجديدها، كان له أثر على الارتقاء بكل الميادين و المجالات الثقافية والأدبية السياسية وغيرها، فانعكست إيجابا على المسرح بمختلف جوانبه باستخدام أحدث التقنيات الحضارية من عروض فيديو، مؤثرات بصرية، تقنيات ضوئية، بالإضافة إلى تقنيات حديثة تساعد على تصميم الصور الملائمة للمسرحيات خاصة المسرحيات الثورية والتي كان لها نصيب كبير في المسارح الجزائرية والعالمية، فلمحاولة تطوير هذا الفن المسرحي الثوري وجب استثمار هذه التقنيات في التجسيد الفعلي لمعالم الثورة الجزائرية. : Abstract Digitization is considered one of the most important topics in the current era, with the scientific and technological development-taking place, as well as the development and renewal of technical media. It had an impact on upgrading all cultural, literary, political and other fields. It was positively reflected on the theater in all its aspects, using the latest civilizational technologies such as video shows, visual effects, lighting techniques, in addition to modern techniques that help to design the appropriate images for plays, especially revolutionary plays, which had a large share in Algerian and international theaters. In order to try to develop this revolutionary theatrical art, these techniques must be invested in the actual embodiment of the features of the Algerian revolution
The impact of technical and technological media on the revolution’s theater
مقال
Keywords: الرقمنة؛الثورة الجزائرية؛ المسرح؛ الوسائط التقنية والتكنولوجية؛ مسرحيات; Digitization; the Algerian revolution;theater; technical and technological media; plays